ILMU BAHASA DAN IMPLIKASINYA DALAM - Suyitno, Imam (Diksi, 2006)
Before linguistics began to have its own paradigms, studies on languagehad been made by using paradigms derived from other disciplines. Language wasdescribed from the view points of philosophy, mechanistic physics, and biology.The studies could not answer questions about what language really is. Whenlinguistics finally had its own paradigms and established itself as an autonomousdiscipline, its studies on language could satisfactorily explain the nature oflanguage and answer questions about the ontology of language. Since thatmoment, studies on language have been growing up enormously and their findingsare significantly giving colors to linguistic studies. The development of linguisticstudies has implied and carried out changes in the orientation of language teachingin general and the teaching and learning of Bahasa Indonesia in particular.Keywords: linguistics, standard grammar, language teaching